2016
DOI: 10.3945/an.116.012518
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein and Zinc Transporter Expression in Circulating Human Blood Cells as Biomarkers of Zinc Status: a Systematic Review

Abstract: Zinc is an essential nutrient for humans; however, a sensitive biomarker to assess zinc status has not been identified. The objective of this systematic review was to compile and assess studies that determined zinc transporter and/or metallothionein expression in various blood cell types and to determine their reliability and sensitivity to changes in dietary zinc. Sixteen studies were identified that determined the expression of zrt-, irt-like protein (ZIP) 1 [solute carrier family (SLC) 39A1], ZIP3 (SLC39A3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 46 publications
2
31
0
1
Order By: Relevance
“…In the present study, it was observed that DMH treated rats supplemented with zinc from the initiation stage resulted in a significant increase in colonic MT mRNA in both precancerous and cancerous groups (3.6 fold and 33 fold respectively), which was reflected in the simultaneous increase in the immunohistochemical localisation of the MT protein (290%, cancer group) along with a concomitant raise in MT protein content (143%, cancer group) as compared with the DMH test group. Our results are in agreement with other studies that zinc supplementation has an effect on MT concentration and its mRNA synthesis in various tissues of growing rats, including esophagus and intestine (Liu et al, 2005) and in human Leukocytes (Hennigar, et al, 2016). These studies demonstrate the responsiveness of MT expression to zinc consumption in humans and rats and are enhanced by observations that zinc increases the susceptibility of cells to apoptosis (Kocdor et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it was observed that DMH treated rats supplemented with zinc from the initiation stage resulted in a significant increase in colonic MT mRNA in both precancerous and cancerous groups (3.6 fold and 33 fold respectively), which was reflected in the simultaneous increase in the immunohistochemical localisation of the MT protein (290%, cancer group) along with a concomitant raise in MT protein content (143%, cancer group) as compared with the DMH test group. Our results are in agreement with other studies that zinc supplementation has an effect on MT concentration and its mRNA synthesis in various tissues of growing rats, including esophagus and intestine (Liu et al, 2005) and in human Leukocytes (Hennigar, et al, 2016). These studies demonstrate the responsiveness of MT expression to zinc consumption in humans and rats and are enhanced by observations that zinc increases the susceptibility of cells to apoptosis (Kocdor et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Metallothioneins are intracellular proteins that can store Zn. Their expression, as well as expression of Zn transporters such as zip-3, is regulated by intracellular levels of Zn [87]. Altogether, these results suggest that host-associated bacteria may play an important role in the uptake of metals (especially Zn) by Drosophila larvae.…”
Section: The Ability Of Bacteria To Compensate Nutritional Deficiencimentioning
confidence: 86%
“…In the T2DM cohort, serum tubes were used for (3 of 9) 1600838 glucose and insulin analyses, and EDTA tubes for analysis of HbA1c. Details on blood collection and biochemical analyses were described previously [9][10][11]16].…”
Section: Blood Collection and Biochemical Analysesmentioning
confidence: 99%